2022
DOI: 10.1021/acssuschemeng.2c06492
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient H2O2 Electrogeneration Enabled by Controlling the Wettability of Gas Diffusion Electrodes and the Reaction Pathway in Divided Cells

Abstract: Efficient electrochemical synthesis of H 2 O 2 via a two-electron oxygen reduction reaction (2e − -ORR) has been intensively pursued in the past few years, yet its potential application is still challenging due to the slow transportation of gaseous reactants and numerous competitive reactions in the electrolytic cell. Herein, we report that efficient electrochemical production of H 2 O 2 can be achieved via tuning the wettability of the gas diffusion electrode (GDE) to the Wenzel−Cassie coexistence state (WCS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…alleviate or even lift the gas diffusion limitation. Wang et al [119] reported an economical commercial CB-based GDE with efficient H 2 O 2 production by tuning the wettability of the GDE. A quasicontinuous gas layer forms over the textured surface of the electrode due to the high hydrophobicity of the catalyst layer, which improves gas transmission (Figure 9a).…”
Section: Device Setup For 2e − Orr To H 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…alleviate or even lift the gas diffusion limitation. Wang et al [119] reported an economical commercial CB-based GDE with efficient H 2 O 2 production by tuning the wettability of the GDE. A quasicontinuous gas layer forms over the textured surface of the electrode due to the high hydrophobicity of the catalyst layer, which improves gas transmission (Figure 9a).…”
Section: Device Setup For 2e − Orr To H 2 Omentioning
confidence: 99%
“…It turns out that when supporting on GDE (Figure 9c), Ni 3 (HITP) 2 exhibits ORR activity and H 2 O 2 electrosynthesis rates >100-fold higher and >740-fold higher, respectively, than in an H-cell. [119] Copyright 2023, American Chemical Society. b) Possible reaction process on AC@Ti-F GDE cathode for boosting H 2 O 2 .…”
Section: Device Setup For 2e − Orr To H 2 Omentioning
confidence: 99%
“…25,26 For instance, micro-/ nanostructured electrodes can be used in gas evolution reactions owing to the significantly depressed bubble adhesion, while superaerophilic electrodes are used for gas consumption reactions due to their ideal gas affinity, both attracting considerable interest. 4,26,27 Typically, the bubble evolution process on the electrode experiences nucleation, growth, and detachment, commonly accompanied by bubble transportation and/or coalescence. 28,29 Bubbles commonly nucleate in cavities or defects of electrodes with nanometer size (it might nucleate at the boundaries if the defect is too big) 30 and grow up by absorbing surrounding supersaturated gas molecules until the buoyancy is large enough to overcome the adhesive force to accomplish the detachment.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of synthesis and manufacturing techniques in recent decades, micro-/nanostructured electrodes, with combined distinctive structures and the intrinsic materials properties, has been gaining tremendous attention. With tunable wettability and multifunctionality, micro-/nanostructured electrodes have exhibited enormous application potential in many fields. Specifically, the concept of gas superwetting (superaerophilic/superaerophobic) electrodes based on micro-/nanostructures has been widely recognized, which triggered substantial revolutions in gas involving electrochemical reactions. , For instance, micro-/nanostructured electrodes can be used in gas evolution reactions owing to the significantly depressed bubble adhesion, while superaerophilic electrodes are used for gas consumption reactions due to their ideal gas affinity, both attracting considerable interest. ,, Typically, the bubble evolution process on the electrode experiences nucleation, growth, and detachment, commonly accompanied by bubble transportation and/or coalescence. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional gas diffusion cathodes (GDE) still need O 2 /air supplement with additional aeration to generate H 2 O 2 , which increases the auxiliary energy input (∼15.6 g kWh –1 , ∼10 times of electrical synthesis energy) . The three interfaces (liquid–gas–solid, Wenzel–Cassie coexistence state) of natural air-diffusion structures (NAD) could provide high oxygen content (∼284 mg L –1 ) and diffusion property (diffusion coefficient: 2.0 × 10 –1 cm 2 s –1 ) in the air, which are designed to obtain excellent faradic efficiency for H 2 O 2 production. Based on various porous carbon materials (i.e., carbon felt, carbon cloth, and carbon paper), the above-mentioned operation mode can significantly reduce electrical energy without an aeration device. Therefore, a highly efficient heterogeneous EF process should integrate the natural air-diffusion cathode for deep investigation.…”
Section: Introductionmentioning
confidence: 99%